AUDIT SYARIAH SEBAGAI PERMASALAHAN ATAU SOLUSI UNTUK PERKEMBANGAN LEMBAGA KEUANGAN SYARIAH YANG TERDAMPAK COVID-19 - Sophia Andini; Paulus Sugito (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2021)
This study aims to determine the factors affecting sharia audit on sharia Financial Institution. These factors include auditor competencies, process audit and Sharia framework. This study used population of external auditor on Public Accounting Firm that having audit sharia financial Institution on Covid-19 situation. In addition, this study analyzed the impact of independent variables to practice of audit sharia as dependent variable using regression analysis. Sampling was carried out in this study using purposive sampling method, which is a sampling method based on the answer of questioner respondence to external auditor audited Sharia Financial Institution. This study states that the auditor competencies and audit process have no effect to the audit sharia, other than Sharia Framework that has effect to it on Covid-19 situation. Keywords: sharia audit, auditor competencies, audit process, sharia framework, covid-19